2018
DOI: 10.1039/c8ta01341a
|View full text |Cite|
|
Sign up to set email alerts
|

In situ study of strontium segregation in La0.6Sr0.4Co0.2Fe0.8O3−δ in ambient atmospheres using high-temperature environmental scanning electron microscopy

Abstract: Samples of the solid oxide fuel cell cathode material La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) were annealed using HT-ESEM from room temperature to 1000 °C in atmospheres of pure oxygen, pure water and ambient lab air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 45 publications
4
71
0
Order By: Relevance
“…Moreover, the lms neither show the expected Sr segregation nor the formation of insulating, Sr-rich clusters upon prolonged (>5 h) annealing at 700 C and 0.2 mbar O 2 : the A-site-to-Mn and the La-to-Sr XPS intensity ratios stay unaltered, and the surface structures appear unchanged in STM, always retaining atomically at morphologies. It is likely that the Sr segregation observed in polycrystalline and textured lms and in ceramic samples under comparable conditions is due to grain and twin boundaries that favor Sr diffusion, 97,98 which are absent in the single-crystalline lms presented here. It is also possible that the epitaxial strain imposed by the SrTiO 3 substrate has a role in suppressing Sr segregation.…”
Section: Origin Of the Surface Reconstructionsmentioning
confidence: 82%
“…Moreover, the lms neither show the expected Sr segregation nor the formation of insulating, Sr-rich clusters upon prolonged (>5 h) annealing at 700 C and 0.2 mbar O 2 : the A-site-to-Mn and the La-to-Sr XPS intensity ratios stay unaltered, and the surface structures appear unchanged in STM, always retaining atomically at morphologies. It is likely that the Sr segregation observed in polycrystalline and textured lms and in ceramic samples under comparable conditions is due to grain and twin boundaries that favor Sr diffusion, 97,98 which are absent in the single-crystalline lms presented here. It is also possible that the epitaxial strain imposed by the SrTiO 3 substrate has a role in suppressing Sr segregation.…”
Section: Origin Of the Surface Reconstructionsmentioning
confidence: 82%
“…On the other hand, grain size determines the amount of grain boundaries which can act as a sink or source of impurities or nucleation sites for secondary phases. 61 Therefore, grain size can affect the rate at which the samples deactivate at 650°C following the high-temperature treatment. We estimate that the density of grain boundaries is approximately 40x greater in LSF than in LSC, which could explain why k chem values are only affected by a factor of 2-3 in case of LSC, while a 30x difference between the activated and passivated states was observed in case of LSF.…”
Section: Effect Of Microstructurementioning
confidence: 99%
“…Niania et al. analyzed the composition of crystallites formed on the surface of LSCF6428 after annealing at high temperatures in dry and humid atmospheres by Auger electron spectroscopy (AES) and low energy ion scattering (LEIS). The authors found strong segregation of strontium to the surface and concluded that the crystallites are Sr‐based compounds.…”
Section: Resultsmentioning
confidence: 92%
“…This is quite reasonable, considering that for mixed‐conducting electrodes this frequency region is commonly assigned to the actual electrode processes encompassing a series of surface‐based elementary reactions (molecular oxygen adsorption, reduction, dissociation, and incorporation into the bulk ). These reactions are strongly affected by modifications of the electrode surface induced either directly by H 2 O (g) or indirectly by poisoning with critical impurities (Cr, Si, etc. ), due to their enhanced gas phase transport in humid atmospheres .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation